2015
DOI: 10.1002/jso.24006
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating resident/fellow training into a robotic surgery program

Abstract: With the rapid uptake of the robotic approach in gynecologic surgery, a thorough understanding of the technology, including its uses and limitations, is critical to maximize patient outcomes and safety. This review discusses the role of training modalities and development of curricula for robotic surgery. Furthermore, methods for incorporating the entire surgical team and the process of credentialing/maintaining privileges are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Previous research has shown that a comprehensive training for robotic surgery was associated with high reliability and significant educational benefit [6,15]. In one such study, 55 participants from general surgery, urology and gynecology were enrolled in a 2-month curriculum that included the following: online didactics, hands-on tutorials, and nine inanimate tasks modified from the Fundamentals of Laparoscopic Surgery program [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that a comprehensive training for robotic surgery was associated with high reliability and significant educational benefit [6,15]. In one such study, 55 participants from general surgery, urology and gynecology were enrolled in a 2-month curriculum that included the following: online didactics, hands-on tutorials, and nine inanimate tasks modified from the Fundamentals of Laparoscopic Surgery program [15].…”
Section: Discussionmentioning
confidence: 99%
“…The development of structured curriculum should consist of clear objectives and goals, a wide variety of training modalities, and be completed in a reasonable timeframe [6]. As time and access were identified as major barriers to robotic training, residency programs should consider incorporating robotic training into protected didactics time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of adverse events caused by actions outside of the surgeon's console is becoming better understood. 1618 Integrating NTS assessment into the curriculum could help prepare the next generation of surgeons to confront the unique challenges of the robotic operating theatre. We initially incorporated the National Aeronautics and Space Administration Task Load Index to capture NTS metrics but due to low compliance, we were not able to show any correlating data.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no evaluation system or definitive number of cases agreed upon to achieve proficiency. 38 In our literature search, the minimal number of cases in other specialties ranged from 10 to 20 cases. 39,40 Our survey responses also showed that most I6 program directors believed that trainees must perform at least 10 robotic surgery cases as a primary bedside assistant during residency (Table 3).…”
Section: Discussionmentioning
confidence: 99%